Raising Awareness of Female Genital Mutilation Through Theater - Cavallaro, Dani (Violence against women, 2023)
This article considers several plays by European playwrights that focus on cases of female genital mutilation, with the goal of raising awareness among their communities of the practice itself, the reason it exists or persists, and the consequences it has had on the lives of the women who have undergone it. The plays discussed are “Kubra” by Dacia Maraini (2016); Little Stitches by Bahar Brunton, Karis E. Halsall, Isley Lynn and Raúl Quirós Molina (2014); and Cuttin’ It by Charlene James (2016).